Playing Across the 'Halfway Line' on the Fields of International Relations: The Journey from Globalising Sport to Sport Diplomacy. (May 2020) - Vonnard, Philippe; Marston, Kevin Tallec
Abstract : On the still divided Joseon peninsula, a united Korean women's ice hockey team competed at the Pyeongchang 2018 Winter Olympics. Only a few months later, the French, Croatian and Russian heads of state quite literally invited themselves on to the winners' podium at the 2018 FIFA men's World Cup in Moscow. Such conspicuous examples are emblematic of the role of modern sport in the realm of international relations.